Gibberellins pre-treatment and storage at high relative humidity improved the quality of 'Eureka' lemon (Citrus limon (L.) Burm. f.) - Dandan Li; Xihong Li; Ze Miao; Jin Du; Jinxiao Cheng; Shiting Hu; Yuhang Li; Yingying Zhang; Lingling Liu; Amr Farouk; Lu Li; Yuqian Jiang (Food Innovation and Advances)
The loss of pericarp greenness, wrinkling of the pericarp, and alteration of aroma are indicators of the ripening and senescence of lemons. In this study, lemons were soaked in 100 mg∙L-1 of gibberellin (GA) solutions for 5 min and stored at 14°C for 36 d under three relative humidity (RH) levels of 30%, 60%, and 90%, respectively. The changes in visual appearance, pigment metabolism, pericarpic microstructure, and volatile compounds of lemons during storage were evaluated. The results showed that GA pretreatment inhibited the color transformation from green to yellow of the flavedo and restrained fruit senescence. In addition, RH 90% effectively maintained the structural integrity of the oil gland, waxes, and stomata in the flavedo. GAs + RH 90% treatment maintained the fruit color index (L*, a*, b*, a*/b*, H°, C*) by inhibiting chlorophyll degradation and regulating carotenoid biosynthesis. Green lemons treated with GAs + RH 90% also showed reduced epidermal wrinkling, well-preserved cuticle, and stomatal structure, with a smooth and intact wax layer on the lemon pericarp. In addition, GAs + RH 90% treatment maintained the content of volatile aroma compounds, especially terpene. GAs + RH 90% had a great advantage in maintaining visual quality, delaying the deformation of tissue microstructure, preserving nutritional quality, and improving aroma. Thus, this treatment is potentially applicable for maintaining the storage quality of green lemons and extending their shelf life.